Teaching Taxes–An Assist. - Sommerfeld, Ray (The Accounting Review, 1965)
Abstract The article presents a critical-path notation that can be used effectively in teaching tax provisions. Tax accounting professors emphasizing the current provisions approach to the study of income taxation would do well to consider utilization of this technique in explaining to students some of the more complicated provisions. The illustration given in this article is based upon the 1964 provisions applicable to the sick-pay exclusion. This particular provision, incidentally, incorporates both the pre-1964 rules and the revisions thereto. The author has discovered that the utilization of such a diagram greatly facilitates an otherwise labyrinth communications problem in tax accounting lectures.